Odpowiedzi

2010-03-10T17:57:14+01:00
A) -2,2+X=6,1
x=6,1+2,2=8,3
b) -1/3y=10/*(-3)
y=-30
c) 6b-3=-9
6b=-9+3
6b=-6/:6
b=1
d) 0=(x-1)-(3x-5)
0=x-1-3x+5
-x+3x=5-1
2x=4/:2
x=2
e) 3(1-x)-(1-2x)=9
3-3x-1+2x=9
-3x+2x=9-3+1
-x=7/:(-1)
x=-7
2010-03-10T18:02:39+01:00
A)x=6,1+2,2 x=8,3
b)-1/3y=10 /:(-1/3) y=-30
c) 6b=-9+3 6b=-6 /:6 b=-1
d)0=x-1-3x+5 0=-2x+4 2x=4/:2 x=2
e)3-3x-1+2x=9 2-x=9 -x=9-2 -x=7 x=-7
Najlepsza Odpowiedź!
2010-03-10T18:25:56+01:00
A) -2,2+X=6,1
x= 6,1+2,2
x=8,3
b) -1/3y=10/*(-3)
y=-30
c) 6b-3=-9
6b= -6/:6
b=1
d) 0=(x-1)-(3x-5)
0= x-1-3x+5
0= -2x+4
2x=4/:2
x=2
e) 3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x=7
x=-7